Factors associated with poor presenting vision among patients with microbial keratitis In Uganda - Arunga, S.; Atto, G.; Ayebazibwe, B.; Onyango, J.; Macleod, D.; Hu, V. H.; Burton, M. J. (The Journal of Ophthalmology of Eastern, Central and Southern Africa, 2020)
To determine factors associated with poor presenting vision among patients with microbial keratitis in Uganda. Design: Retrospective audit study. Methods: This was a study of patients presenting with microbial keratitis at the two main eye units in Southern Uganda in the year 2015. Information on time to presentation, treatment history, use of traditional eye medicine, trauma and presenting final visual acuity was collected. Factors associated with a poor presenting vision in a regression model were analysed. Results: There were 273 cases during the year 2015. The median presentation time was 7 days from onset (IQR 2-21, total range 0-366 days). Trauma was reported in 59/88 (67%) patients and 69/162 (43%) reported using traditional eye medicine. Visual acuity was reported in only 216/273 cases at presention. Visual acuity at presentation of less than 6/60 (severe visual impairment) was strongly associated with the use of traditional eye medicine (OR 5.13, 95%CI 2.17–12.1, p=0.001) and distance from the eye hospital (OR 1.02, 95% CI 1.01-1.03, p=0.002). Conclusion: This audit highlighted the role of use of traditional eye medicine and long distance from the eye hospital in contributing to poor presentation among patients with microbial keratitis in Uganda.
Keywords: Microbial keratitis; Bacterial keratitis; Fungal keratitis; Keratitis; Traditional eye medicine